2018
DOI: 10.1111/jrh.12326
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Alcohol Use Among Patients Living With HIV in Urban, Large Rural, and Small Rural Areas

Abstract: Background For people living with HIV (PLWH), alcohol use is harmful and may be influenced by unique challenges faced by PLWH living in rural areas. We describe patterns of alcohol use across rurality among PLWH. Methods Veterans Aging Cohort Study electronic health record data were used to identify patients with HIV (ICD‐9 codes for HIV or AIDS) who completed AUDIT‐C alcohol screening between February 1, 2008, and September 30, 2014. Regression models estimated and compared 4 alcohol use outcomes (any use [AU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…For a scholarly review of AUD-HIV-HCV comorbidity with psychiatry, medication, and aging also considered, see Zahr (2018a). The U.S. Veterans Aging Cohort study found that the AUD prevalence rate of 32,699 people living with HIV ranged from 11.8% in rural areas to 14.4% in urban settings (Bensley et al, 2018). The comorbidities of AUD, HIV, and HCV take a toll on brain structure (Gullett et al, 2018; Pfefferbaum, Kwon et al, 2018) and function (Fama, Sullivan, Sassoon, Pfefferbaum, & Zahr, 2016; Gongvatana et al, 2014) possibly through a combination of inflammatory mechanisms stemming especially from HCV (Zahr, 2018b), interference of antiretroviral action from alcohol (Simon et al, 2018), or risk of nonadherence associated with drinking (Paolillo, Gongvatana, Umlauf, Letendre, & Moore, 2017) or drug use whether licit or illicit (Malbergier, Amaral, & Cardoso, 2015; but see Nolan et al, 2017).…”
Section: Common Comorbidities Of Aud: Contribution To Impairmentmentioning
confidence: 99%
“…For a scholarly review of AUD-HIV-HCV comorbidity with psychiatry, medication, and aging also considered, see Zahr (2018a). The U.S. Veterans Aging Cohort study found that the AUD prevalence rate of 32,699 people living with HIV ranged from 11.8% in rural areas to 14.4% in urban settings (Bensley et al, 2018). The comorbidities of AUD, HIV, and HCV take a toll on brain structure (Gullett et al, 2018; Pfefferbaum, Kwon et al, 2018) and function (Fama, Sullivan, Sassoon, Pfefferbaum, & Zahr, 2016; Gongvatana et al, 2014) possibly through a combination of inflammatory mechanisms stemming especially from HCV (Zahr, 2018b), interference of antiretroviral action from alcohol (Simon et al, 2018), or risk of nonadherence associated with drinking (Paolillo, Gongvatana, Umlauf, Letendre, & Moore, 2017) or drug use whether licit or illicit (Malbergier, Amaral, & Cardoso, 2015; but see Nolan et al, 2017).…”
Section: Common Comorbidities Of Aud: Contribution To Impairmentmentioning
confidence: 99%
“…Modifiable factors such as alcohol use are thought to accelerate aging in the general population 6 and may contribute to frailty among PLWH on cART. Alcohol use is prevalent in 50-66% of PLWH [7][8][9][10] . Nearly 27% of PLWH consume potentially hazardous quantities of alcohol 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 27% of PLWH consume potentially hazardous quantities of alcohol 9,10 . An estimated 12-14% of PLWH may meet the criteria for an alcohol use disorder 8 . Interestingly, PLWH with a history of alcohol-related health complications are at an increased risk for hospitalization 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Among people living with HIV, the prevalence of AUD is nearly 15% in urban settings (Bensley et al, 2019). HIV+AUD comorbidity has the potential of compounding effects to cognitive deficits, noted in executive functioning, memory, and psychomotor and visuomotor speed (Cardenas et al, 2005;Durvasula et al, 2006;Fama, Rosenbloom et al, 2012;Fama et al, 2016;Saloner et al, 2020).…”
Section: Cognitive and Motor Processesmentioning
confidence: 99%